A descriptive study of IgG subclasses and allotypes in children with pulmonary tuberculosis in the Western Cape - Potgieter, Stephanus Theron (Division of Pulmonology, 2017)
STUDY OBJECTIVES: An analysis of IgG subclasses and allotypes in children with pulmonary Tuberculosis (PTB) in the Western Cape. DESIGN: Consecutive children under 15 years of age with microbiological proven PTB over an 8 month period- November 1993 to July 1994. SETTING: Teaching Hospitals in Cape Town. PATIENTS: Thirty-five cases were selected from 99 consecutive cases that were Mycobacterium tuberculosis positive, 15 of which were of Mixed and 20 were of Black Ancestry. CONTROL GROUP: Sera were selected from 224 Black Ancestry (59 children and 165 adults) and 211 Mixed Ancestry (67 children and 144 adults) that had no evidence for active tuberculosis or a history of previous TB diagnosis. MEASUREMENTS AND RESULTS: IgG subclasses, total IgG,and five allotypes: Glm(a), Glm(f), G2m(n), G3m(bl), G3m(gl) were determined by ELISA techniques. In the Mixed ancestry group the Glm(f) (p= 0.01), G2m(n) (p= 0.04) and G3m(gl) (p=0.001) allotypes were less frequently found in children with proven PTB. In the Black Ancestry subjects the G3m(g 1) allotype was significantly less common than in the control group (p < 0.001). CONCLUSIONS: Because allotypes are inherited in a Mendelian fashion, the observed association of childhood PTB and certain allotypes strengthens the hypothesis that a genetic susceptibility exists to acquiring TB.